Acmaeodera (Ptychomus) kubani sp.n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini) - Volkovitsh, Mark G. (Zootaxa, 2018)
Acmaeodera (Ptychomus) kubani sp. n. from Algeria, Libya and Egypt together with A. (P.) kubani saudita subsp. n. from Saudi Arabia are described, illustrated and compared with closely related species. Species-groups A. (P.) arabica Gory, 1840, A. (P.) polita (Klug, 1829) (with A. polita and A. foudrasii Solier, 1833 subgroups) and A. (P.) argodi Kerremans, 1907 are established within subgenus Ptychomus Marseul, 1866; diagnostic characters and composition of these groups are discussed.